2022
DOI: 10.1177/20597002221133183
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging correlates of syndromal depression following traumatic brain injury: A systematic review of the literature

Abstract: Objective To complete a systematic review of the literature examining neuroimaging findings unique to co-occurring syndromal depression in the setting of TBI. Methods A PRISMA compliant literature search was conducted in PubMed (MEDLINE), PsychINFO, EMBASE, and Scopus databases for articles published prior to April of 2022. The database query yielded 4447 unique articles. These articles were narrowed based on specific inclusion criteria (e.g., clear TBI definition, clear depression construct commenting on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Reviews of depressive disorders, 22 anxiety disorders, 23 obsessive-compulsive disorders 24 and post-traumatic stress disorder (PTSD) 25 showed that regional associations found within individual studies could not be reliably synthesised. [22][23][24][25] The lack of consensus on reliable neuroimaging markers of psychopathology after TBI may reflect the significant heterogeneity of injury after TBI, but also could be attributed to limitations of categorical psychopathology. For example, mixed neurobiological findings may arise due to the heterogeneity of symptoms within diagnostic groups.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews of depressive disorders, 22 anxiety disorders, 23 obsessive-compulsive disorders 24 and post-traumatic stress disorder (PTSD) 25 showed that regional associations found within individual studies could not be reliably synthesised. [22][23][24][25] The lack of consensus on reliable neuroimaging markers of psychopathology after TBI may reflect the significant heterogeneity of injury after TBI, but also could be attributed to limitations of categorical psychopathology. For example, mixed neurobiological findings may arise due to the heterogeneity of symptoms within diagnostic groups.…”
Section: Open Accessmentioning
confidence: 99%
“…These investigations, however, focus on specific disorders. Reviews of depressive disorders,22 anxiety disorders,23 obsessive-compulsive disorders24 and post-traumatic stress disorder (PTSD)25 showed that regional associations found within individual studies could not be reliably synthesised 22–25…”
Section: Introductionmentioning
confidence: 99%
“…These investigations, however, focus on specific disorders. Reviews of depressive disorders [22], anxiety disorders [23], obsessivecompulsive disorders [24] and PTSD [25] showed that regional associations found within individual studies could not be reliably synthesised [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%